TRANSLATION ANALYSIS OF IDIOMS IN NOVEL CRAZY RICH ASIANS: SEMANTIC APPROACH - Risma Yulianti; Evert Haryanto Hilman; Maftuchah Dwi Agustina (IdeBahasa, 2022)
The purpose of the research is to figure out how to translate idioms from English into Indonesian. The data were taken from a novel Crazy Rich Asian by Kevin Kwan and its translation into Kaya Tujuh Turunan by Cindy Kristanto. Because the meaning of an idiom cannot be translated from each of its terms, the application of appropriate methodologies to translate idioms affects the idiom translation. Many English idioms have the same meaning as idiomatic expressions, but they are expressed in different ways. Other idioms do not have equivalent idioms, so they were translated using the free translation method.. The method of this study is a descriptive qualitative method research. There were 325 data which were analyzed qualitatively to determine the types of idioms and what semantic strategies were employed. The result shows that paraphrase dominated of all idiom types with 83 data, followed by synonym 73 data, Emphasis change 66 data, abstraction change 62 data and distribution change 41 data. The author conducted research on the relevance of understanding idioms and how to use them more effectively.